IMPROVEMENT OF THE CHX-3M2 LARGE DIRT CLEANING EQUIPMENT BRUSH (Journal of Science-Innovative Research in Uzbekistan, 2024)
Cleaning equipment included in the technological process of initial processing of seed cotton in cotton ginning enterprises is installed in the cleaning departments of this enterprise, and their location can be different